Effect of Varying Alkyl Chain Length on Thermal Decomposition Temperature of Zinc(II) Xanthates and its Impact on Curing of Epoxy Resin1. Issue 2 (30th November 2015) - Vagvala, Tarun Chand; Pandey, Shyam Sudhir; Krishnamurthy, Suvratha; Hayase, Shuzi
Abstract: Linear and branched zinc(II) xanthates with varying alkyl chain length were synthesized and characterized by 1 H NMR, 13 C NMR, and IR spectroscopy, as well as elemental analysis. Zinc sulfide as the final decomposition product upon thermal annealing of zinc(II) xanthates was confirmed by XRD analysis. Cure time for epoxy resin composite at various temperatures was analyzed employing zinc(II) xanthates (5 % mass) as latent cure catalysts. XRD investigation of the cured epoxy resin including zinc(II) xanthates upon thermal annealing revealed the presence of ZnS in‐situ in the composite matrix, indicating the in‐situ thermal decomposition of zinc(II) xanthates as probable mechanism for curing. Thermogravimetric analysis was performed to investigate the thermal decomposition temperature trend of zinc(II) xanthates. A parallel trend was observed correlating the thermal decomposition temperature trend of zinc(II) xanthates and the order of curing catalytic efficiency utilizing zinc(II) xanthates. In the case of linear alkylzinc(II) xanthates with an increase in the alkyl chain length, both thermal decomposition temperature and the cure time were enhanced. In contrast, in case of branched alkyl chain zinc(II) xanthates with increasing alkyl chain length show decreasing thermal decomposition temperature as well as cure time. Abstract :